Polynitrile compound, non-aqueous electrolyte and lithium ion battery
By using polynitrile compounds as electrolyte additives in lithium-ion batteries to form a stable interface film and inorganic SEI film, the performance problems of lithium-ion batteries under high voltage and high temperature conditions are solved, and better circulation and storage performance are achieved.
Patent Information
- Application Number
- CN202310487988.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-05-04
AI Technical Summary
Under high voltage and high temperature conditions, the positive electrode material is prone to O3→H1-3→O1 phase change in existing lithium-ion batteries, resulting in increased internal resistance, huge structural changes, and capacity voltage attenuation. In addition, conventional electrolytes are easily oxidized and decomposed at high voltages, deteriorating the positive electrode material.
Polynitrile compounds are used as additives for electrolytes, and a stable interface film and thinner inorganic SEI film are formed at the interface of the material to inhibit the oxidation and decomposition of the electrolytes, and the stability of the lithium ion channel and the structure of the SEI film are improved.
Improves the cycling and storage performance of lithium-ion batteries under high voltage and high temperature conditions, extends the battery life and improves its performance at low and high temperatures.
Smart Images

Figure QLYQS_1 
Figure BDA0004209174210000021 
Figure BDA0004209174210000022
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a polynitrile compound, a non-aqueous electrolyte thereof and a lithium ion battery. Background Art
[0002] As the requirements for secondary battery capacity in pure electric vehicles, hybrid electric vehicles and portable energy storage devices continue to increase, people are looking forward to developing secondary batteries with higher energy density and power density to achieve energy storage and long-term endurance.
[0003] In addition to the improvement of existing materials and battery manufacturing processes, high-voltage positive electrode materials are one of the more popular research directions, which achieves high energy density of batteries by increasing the charging depth of positive electrode active materials. Among them, lithium cobalt oxide materials are prone to O3→H1-3→O1 phase transition under high voltage and high temperature, which is mainly manifested as: 1. The phase transition kinetics deteriorate, resulting in an increase in internal resistance at high potential; 2. The structure changes drastically, and the O3 structure disappears; 3. The unit cell parameters expand and contract violently; 4. The slip phase transition is not completely reversible, causing capacity and voltage decay. The macroscopic manifestation of the drastic change in unit cell parameters causes the volume of material particles to expand and contract, and at the same time, the change in particles causes changes in electrode materials and causes battery cell decay. In addition, conventional carbonate electrolytes will oxidize and decompose on the surface of the positive electrode of the battery at a high voltage of 4.5V, especially under high temperature conditions, which will accelerate the oxidation and decomposition of the electrolyte and promote the deterioration reaction of the positive electrode material.
[0004] Therefore, it is necessary to develop an electrolyte that can withstand a high voltage of 4.5V to achieve excellent electrical performance of lithium-ion batteries. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a polynitrile compound, a non-aqueous electrolyte and a lithium ion battery, wherein the polynitrile compound can reduce the surface activity of the positive electrode material and thus inhibit the oxidative decomposition of the electrolyte, so as to improve the high temperature storage and cycle performance of a high voltage (4.5V) lithium cobalt oxide system lithium ion battery.
[0006] To achieve the above object, the present invention provides a polynitrile compound in the first aspect, the structural formula of which is shown in Structural Formula I or Structural Formula II, wherein R 1 ~R 2 Each is independently selected from halogen, a halogen-substituted C1-C6 hydrocarbon group, a group containing a halogen-substituted sulfonate group, a group containing a halogen-substituted sulfone group or a group containing a halogen-substituted phosphonate group.
[0007]
[0008] The polynitrile compound of the present invention is used as an electrolyte, and a stable interface film can be formed at the interface of the material. The film has a good conductive lithium ion channel, and the lithium ion channel will not collapse during the cycle process, so the cycle and low temperature performance are improved. In addition, the side chain functional group structure containing at least halogen is introduced, which can form a thinner inorganic SEI film, occupy the SEI film site, and can alleviate the problem of impedance increase caused by excessive polymerization of nitriles. At the same time, the SEI film is enriched and stabilized, and the transition metal in the positive electrode material can be complexed, so the low temperature and high temperature storage performance can be improved.
[0009] As a technical solution of the present invention, R 1 ~R 2 Each is independently selected from a fluorine-substituted C1-C3 alkyl group, a group containing a fluorine-substituted sulfonate group, a group containing a fluorine-substituted sulfone group, or a group containing a fluorine-substituted phosphonate group. Sulfonate groups, sulfone groups, phosphonates, etc. are introduced into the side chain functional group structure, and the rich P, O, S and other elements enrich the electrode / electrolyte interface film components, which can further improve the structural stability of the interface film.
[0010] As a technical solution of the present invention, at least one selected from Compounds 1 to 8,
[0011]
[0012]
[0013] The second aspect of the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises the aforementioned polynitrile compound.
[0014] As a technical solution of the present invention, the polynitrile compound accounts for 0.1-5.0% of the total mass of the non-aqueous organic solvent, the electrolyte salt and the additive. Preferably, the polynitrile compound accounts for 0.1-3.0% of the total mass of the non-aqueous organic solvent, the electrolyte salt and the additive. As an example, the proportion of the polynitrile compound to the total mass of the non-aqueous organic solvent, the electrolyte salt and the additive may be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%.
[0015] As a technical solution of the present invention, the electrolyte salt accounts for 6-15% of the sum of the mass of the non-aqueous organic solvent, the electrolyte salt and the additive. Preferably, the electrolyte salt accounts for 8-15%. As an example, the electrolyte salt may account for, but is not limited to, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%. The electrolyte salt is selected from lithium hexafluorophosphate (LiPF 6), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium methanesulfonate (LiCH 3 SO 3 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), Lithium Bis(trifluoromethanesulfonyl)imide (LiN(CF 3 SO 2 ) 2 ), lithium bis(oxalateborate) 4 BLiO 8 ), lithium difluorooxalate borate (C 2 BF 2 LiO 4 ), lithium difluorophosphate (LiPO 2 F 2 ), at least one of lithium difluorobis(oxalyl)phosphate (LiDFBP), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0016] As a technical solution of the present invention, the non-aqueous organic solvent is at least one of a linear carbonate, a cyclic carbonate and a carboxylate. Preferably, the non-aqueous organic solvent is a mixture of a linear carbonate and a cyclic carbonate. As an example, the non-aqueous organic solvent is selected from at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), butyl acetate (n-Ba), γ-butyrolactone (γ-Bt), propyl propionate (n-Pp), ethyl propionate (EP) and ethyl butyrate (Eb). The non-aqueous organic solvent accounts for ≥80% of the sum of the mass of the non-aqueous organic solvent, electrolyte salt and additive, preferably ≥85%. As an example, the non-aqueous organic solvent accounts for but is not limited to ≥80%, ≥81%, ≥82%, ≥83%, ≥84%, ≥85%, ≥86%, ≥87%, ≥88%, ≥89%, ≥90% of the sum of the mass of the non-aqueous organic solvent, electrolyte salt and additive.
[0017] As a technical solution of the present invention, the additive further includes compound A. Compound A is selected from at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), 1,3-propane sultone (PS) and vinyl sulfate (DTD). Compound A accounts for 0.1 to 10.0% of the total mass of the non-aqueous organic solvent, the electrolyte salt and the additive. Preferably, compound A accounts for 0.1 to 6.0% of the total mass of the non-aqueous organic solvent, the electrolyte salt and the additive. As an example, the proportion of compound A to the sum of the mass of the non-aqueous organic solvent, the electrolyte salt and the additive may be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%.
[0018] The second aspect of the present invention provides a lithium ion battery, comprising a positive electrode material, a negative electrode material and a non-aqueous electrolyte. The lithium ion battery has a good cycle life and high temperature storage performance, which is conducive to the further industrial development of lithium ion batteries.
[0019] As a technical solution of the present invention, the positive electrode material is a cobalt oxide material, and the chemical formula of the cobalt oxide material is LiCo x M y O 2 , wherein 0≤y<0.08, x+y≤1, and M is at least one of Al, Mg, Zr and Ti.
[0020] As a technical solution of the present invention, the negative electrode material is selected from at least one of a carbon-based negative electrode material, a titanium-based oxide negative electrode material and a silicon-based negative electrode material.
[0021] As a technical solution of the present invention, the negative electrode material can be selected from artificial graphite, natural graphite, hard carbon, soft carbon, lithium titanate, Si material, silicon oxygen material or silicon carbon material (10wt.%Si). DETAILED DESCRIPTION
[0022] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0023] Where specific conditions are not specified in the examples, the experiments can be carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used without specifying the manufacturer are all conventional products available from the market.
[0024] The following compounds 1 to 8 of the present invention can be obtained by synthesis.
[0025]
[0026] The synthesis route of compound 2 can be the following route 1.
[0027]
[0028] The specific operation is as follows: add 9.9 g of malononitrile, 200 g of anhydrous acetonitrile and 1.5 g of triethylamine into a three-necked flask filled with nitrogen atmosphere, stir evenly, then slowly drop 33 g of ethylene sulfonyl fluoride, and then react for 4 hours to obtain a deep red solution, then concentrate the solution, add dichloromethane for extraction and crystallization, filter to obtain a slightly yellow solid, and vacuum dry at 120°C to obtain 38.5 g of a solid.
[0029] Compound 1, Compound 3 and Compound 4 were synthesized by referring to route 1 using CAS: 75-02-5, CAS: 55444-21-8 and CAS: 2050472-43-8 to replace ethylene sulfonyl fluoride.
[0030]
[0031] The synthetic route of compound 6 can be the following route 2.
[0032]
[0033] The specific operation is as follows: 16.1 g of 1,3,6-hexanetrinitrile, 100 g of anhydrous acetonitrile and 1.5 g of sodium tert-butoxide are added into a three-necked flask filled with nitrogen atmosphere and stirred evenly, and then 12 g of ethylene sulfonyl fluoride is slowly added dropwise, and then reacted for 24 hours to obtain a deep red solution, and then the solution is concentrated, and dichloromethane is added for extraction and crystallization, and a slightly yellow solid is obtained by filtration, and 23 g of solid is obtained by vacuum drying at 120°C, with a yield of 85%.
[0034] Compound 5, compound 7 and compound 8 were synthesized by referring to route 2 using CAS: 75-02-5, CAS: 55444-21-8 and CAS: 2050472-43-8 respectively to replace ethylene sulfonyl fluoride.
[0035] Example 1
[0036] (1) Preparation of non-aqueous electrolyte: The electrolyte was prepared in a vacuum glove box with an argon atmosphere and a moisture content of less than 1 ppm. In a dry argon atmosphere glove box, ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a weight ratio of EC:DEC = 3:7, and then compound 1 was added. After dissolving and stirring, lithium hexafluorophosphate was added and mixed well to obtain an electrolyte.
[0037] (2) Preparation of positive electrode: LiCo 0.9 Zr 0.1 O 2 The adhesive PVDF and the conductive agent SuperP are evenly mixed in a mass ratio of 97:1:2 to form a lithium-ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.
[0038] (3) Preparation of negative electrode: Silicon-carbon negative electrode material (10 wt.% Si) is mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 96:1:1:2 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll-press to obtain the negative electrode sheet.
[0039] (4) Preparation of lithium-ion batteries: The positive electrode sheets, separators and negative electrode sheets are stacked to form a square battery cell, which is packaged with a polymer and filled with the above-prepared lithium-ion battery non-aqueous electrolyte. After the steps of formation and capacity separation, a lithium-ion battery with a capacity of 1400 mAh is manufactured.
[0040] The electrolyte formulas of Examples 1 to 14 and Comparative Examples 1 to 8 are shown in Table 1, and the steps of preparing the electrolytes and batteries of Examples 2 to 14 and Comparative Examples 1 to 8 are the same as those of Example 1.
[0041] Table 1 Electrolyte components of various embodiments and comparative examples
[0042]
[0043]
[0044] The lithium ion batteries prepared in Examples 1 to 14 and Comparative Examples 1 to 10 were subjected to normal temperature cycle test, high temperature cycle test, high temperature storage test and low temperature discharge test, respectively. The specific test conditions are as follows. The test results are shown in Table 2.
[0045] (1) Normal temperature cycle test
[0046] At room temperature (25°C), the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0) with an upper limit voltage of 4.5V, and then charged and discharged at 1.0C / 1.0C for 500 cycles at room temperature (the battery discharge capacity is C1).
[0047] Capacity retention rate = (C1 / C0)*100%.
[0048] (2) High temperature cycle test of lithium-ion batteries
[0049] At an over-high temperature (45°C), the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0), with an upper voltage of 4.5V, and then charged and discharged at 1.0C / 1.0C for 300 cycles at room temperature (the battery discharge capacity is C1).
[0050] Capacity retention rate = (C1 / C0)*100%
[0051] (3) High temperature storage test
[0052] At room temperature (25°C), the lithium-ion battery was charged and discharged at 0.3C / 0.3C (the battery discharge capacity was recorded as C 0 ), the upper limit voltage is 4.5V. Place the battery in an 85℃ oven for 6h, take out the battery, place the battery in a 25℃ environment, and discharge it at 0.3C. The discharge capacity is recorded as C 1 The lithium-ion battery was then charged and discharged at 0.3C / 0.3C (the battery discharge capacity was recorded as C 2 ).
[0053] Capacity retention rate = (C 1 / C 0 )*100%
[0054] Capacity recovery rate = (C 2 / C 0 )*100%
[0055] Low temperature discharge test
[0056] At room temperature (25°C), the lithium-ion battery was charged and discharged at 0.3C / 0.3C (the battery discharge capacity was recorded as C 0 ), the upper voltage limit is 4.5V. The battery is placed in a -20℃ oven for 4h, and the battery is discharged at 0.3C. The discharge capacity is recorded as C 1 , the cut-off voltage is 3.0V.
[0057] Capacity retention rate = (C 1 / C 0 )*100%
[0058] Table 2 Lithium-ion battery performance test results
[0059]
[0060]
[0061] From the results in Table 2, it can be seen that the use of the polynitrile compound of the present invention as an additive can greatly improve the cycle performance, high temperature storage and low temperature discharge performance of the battery. This is because the polynitrile compound can not only form a stable interface film at the interface of the material, but also introduce a side chain functional group structure containing at least halogen, which can form a thinner inorganic SEI film and occupy the SEI film site, which can alleviate the problem of increased impedance caused by excessive polymerization of nitriles. At the same time, it enriches and stabilizes the SEI film and can complex the transition metal in the positive electrode material, so it can improve the low and high temperature storage performance.
[0062] By comparing Examples 1 to 4 with Examples 5 to 8, it can be seen that the battery performance is better when sulfonate, sulfone and phosphonate are introduced into the side chain functional group structure of the selected polynitrile compound. This may be because the rich elements such as P, O and S enrich the components of the electrode / electrolyte interface film, which can further improve the structural stability of the interface film.
[0063] By comparing Example 1, Examples 12 to 14 and Comparative Examples 2 to 4, it can be seen that when compound A is introduced on the basis of the polynitrile compound, especially when compound A contains VC and FEC at the same time, the performance of the lithium ion battery is the best. This may be due to the synergistic effect of VC, FEC and the polynitrile compound: the inorganic SEI formed by FEC may be more resilient, and the organic SEI formed by VC polymerization has better thermal stability. The polynitrile compound of the present invention can be adsorbed at the electrode interface to form an inorganic SEI and an organic adsorption layer, further optimizing the inorganic SEI and improving the stability of the organic interface, and the performance of the battery is significantly improved.
[0064] By comparing Example 5 and Comparative Example 5, it can be seen that although the compound nine in Comparative Example 5 is similar in structure to the compound five in Example 5, the SEI film formed by the trinitrile compound has a larger impedance and there is no halogen-free side chain functional group structure to alleviate the problem of increased impedance, so the battery performance is poor.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polynitrile compound, characterized in that At least one selected from Compound 1 to Compound 8, 2. A non-aqueous electrolyte comprising a non-aqueous organic solvent, an electrolyte salt and an additive, characterized in that: The additive comprises the polynitrile compound according to claim 1.
3. The non-aqueous electrolyte according to claim 2, characterized in that The polynitrile compound accounts for 0.1 to 5.0% of the total mass of the non-aqueous organic solvent, the electrolyte salt and the additive.
4. The non-aqueous electrolyte according to claim 2, characterized in that The electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium methanesulfonate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate, lithium bisfluorosulfonyl imide and lithium bistrifluoromethanesulfonyl imide.
5. The non-aqueous electrolyte according to claim 2, characterized in that The non-aqueous organic solvent is selected from at least one of chain carbonates, cyclic carbonates and carboxylates.
6. The non-aqueous electrolyte according to claim 2, characterized in that The additive further includes a compound A, and the compound A is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfite, 1,3-propane sultone and vinyl sulfate.
7. A lithium ion battery comprising a positive electrode material, a negative electrode material and the non-aqueous electrolyte according to any one of claims 2 to 6.
8. The lithium-ion battery according to claim 7, characterized in that: The positive electrode material is a cobalt oxide material, and the chemical formula of the cobalt oxide material is LiCo x M y O2, wherein 0≤y<0.08, x+y≤1, and M is at least one of Al, Mg, Zr and Ti.
Citation Information
Patent Citations
Mail bag catcher and deliverer
CA75025A
Electrolytic solution, secondary battery, battery pack, electric vehicle, and electric power storage system
CN103178291A
Cyanoalkyl sulfonylfluorides for electrolyte compositions for high energy lithium-ion batteries
CN108475821A
Nitrile compound and its pest control use
CN1898200A